A critical reflection on the use and effectiveness of DVPNs and DVPOs. (15th January 2021) - Blackburn, Kate; Graca, Sofia
ABSTRACT: Domestic Violence Protection Notices (DVPNs) and Domestic Violence Protection Orders (DVPOs) are short-term police-initiated protection mechanisms, aimed at providing victims with time to plan longer-term strategies to escape abusive relationships. Despite being available in England and Wales since 2014, there is relatively little research regarding their use and effectiveness. This article fills this knowledge gap by providing an empirically based 'snapshot' of their use by London's Metropolitan Police Service (MPS), and considers whether they can be deemed successful in their intended outcomes. It does so against the national and international legal context in which the orders were created and the practices and policies used to deploy them (including: management of risk, protection of human rights and combating violence and abuse against women). It also considers the implications of their replacement with Domestic Abuse Protection Notices (DAPNs) and Domestic Abuse Protection Orders (DAPOs), as foreseen by the new Domestic Abuse Bill.